2009
DOI: 10.1007/s00063-009-1070-2
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Prothrombin Time (INR) and Platelets Do Not Increase the Risk of Significant Bleeding when Placing Central Venous Catheters*

Abstract: These findings demonstrate that coagulation disorders with altered prothrombin time (INR) or platelets do not increase the risk of significant bleeding when inserting a central venous catheter. Therefore, the prophylactic correction of coagulation by transfusion of blood products or coagulation factors is not necessary before central venous catheter insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
(31 reference statements)
0
30
0
Order By: Relevance
“…In three of these studies without prophylactic platelet transfusion, thrombocytopenia was identified as a risk factor for local hematoma and oozing. 23,24,41 One study reported no association between thrombocytopenia and minor bleeding complications. 38 In 11 studies, a small group of patients received platelet transfusion.…”
Section: Platelet Countmentioning
confidence: 99%
“…In three of these studies without prophylactic platelet transfusion, thrombocytopenia was identified as a risk factor for local hematoma and oozing. 23,24,41 One study reported no association between thrombocytopenia and minor bleeding complications. 38 In 11 studies, a small group of patients received platelet transfusion.…”
Section: Platelet Countmentioning
confidence: 99%
“…Seventeen observational studies have reported bleeding outcomes in thrombocytopenic patients after insertion of central venous catheters (CVCs) ( Table V). Only one case of severe bleeding (Hb drop >15 g/l) was reported throughout all of these studies (Weigand et al, 2009). Three studies reported on risk factors, in addition to thrombocytopenia, associated with bleeding.…”
Section: Central Venous Cathetersmentioning
confidence: 99%
“…A delay of CVC insertion waiting for blood products seems to be unjustified, particularly in view of complication rates. 10 Another study has concluded that ultrasound guided central venous cannulation in patients with liver disease and coagulopathy is a safe and is a highly successful modality. In their study, mean INR was 2.17 ± 1.16 whereas median platelet count was 149.5 (range 12-683) × 10 9 /L.…”
Section: Discussionmentioning
confidence: 99%